Answering Orientation Questions and Following Single-Step Verbal Commands: Effect on Aspiration Status - Leder, Steven B.; Suiter, Debra M.; Lisitano Warner, Heather (Dysphagia, 2009)
In the acute-care setting patients with altered mental status as a result of such diverse etiologies as stroke, traumatic brain injury, degenerative neurologic impairments, dementia, or alcohol/drug abuse are routinely referred for dysphagia testing. A protocol for dysphagia testing was developed that began with verbal stimuli to determine patient orientation status and ability to follow single-step verbal commands. Although unknown, it would be beneficial to ascertain if this information on mental status was predictive of aspiration risk. The purpose of this investigation was to determine if there was a difference in odds for aspiration based upon correctly answering specific orientation questions, i.e., 1. What is your name? 2. Where are you right now? and 3. What year is it?, and following specific single-step verbal commands, i.e., 1. Open your mouth. 2. Stick out your tongue. and 3. Smile. In a consecutive retrospective manner data from 4070 referred patients accrued between 1 December 1999 and 1 January 2007 were analyzed. The odds of liquid aspiration were 31% greater for patients not oriented to person, place, and time (odds ratio [OR] = 1.305, 95% CI = 1.134–1.501). The odds of liquid aspiration (OR = 1.566, 95% CI = 1.307–1.876), puree aspiration (OR = 1.484, 95% CI = 1.202–1.831), and being deemed unsafe for any oral intake (OR = 1.688, 95% CI = 1.387–2.054) were, respectively, 57, 48, and 69% greater for patients unable to follow single-step verbal commands. Being able to answer orientation questions and follow single-step verbal commands provides information on odds of aspiration for liquid and puree food consistencies as well as overall eating status prior todysphagia testing. Knowledge of potential increased odds of aspiration allows for individualization of dysphagia testing thereby optimizing swallowing success.
Keywords: Aspiration; Cognition; Deglutition; Deglutition disorders; peer-reviewed